PENGARUH PENERAPAN MODEL PEMBELAJARAN CREATIVE PROBLEM SOLVING TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA KELAS XII MATEMATIKA SMA NEGERI 1 LEMBAH GUMANTI - Fadli, Rahmat (Departemen Matematika, 2024)
To help students become better problem solvers in mathematics, teachers can apply the Creative Problem Solving (CPS) model. The objectives of this study were (1) to characterise the development of students' abilities after using the CPS model and (2) to determine whether their abilities were better after using the CPS model than the direct learning model. This study used a quasi-experimental design with a non-equivalent control group with a posttest-only control group. Students using the CPS model outperformed the direct learning method in the skills highlighted in this study.Keywords. –Mathematical Problem-Solving Abilities, Creative Problem Solving, Direct Learning